Kinematic hand parameters in front crawl at different paces of swimming - Samson, M.; Monnet, T.; Bernard, A.; Lacouture, P.; David, L. (Journal of Biomechanics, 2015)
The aim of this study was to investigate the evolution of kinematic hand parameters (sweepback angle, angle of attack, velocity, acceleration and orientation of the hand relative to the absolute coordinate system) throughout an aquatic stroke and to study the possible modifications caused by a variation of the swimming pace. Seventeen competitive swimmers swam at long distance, middle distance and sprint paces. Parameters were calculated from the trajectory of seven markers on the hand measured with an optoelectronic system. Results showed that kinematic hand parameters evolve differently depending on the pace. Angle of attack, sweepback angle, acceleration and orientation of the hand do not vary significantly. The velocity of the hand increases when the pace increases, but only during the less propulsive phases (entry and stretch and downsweep to catch). The more the pace increases and the more the absolute durations of the entry and stretch and downsweep to catch phases decrease. Absolute durations of the insweep and upsweep phases remain constant. During these phases, the propulsive hand forces calculated do not vary significantly when the pace increases. The increase of swimming pace is then explained by the swimmer's capacity to maintain propulsive phases rather than increasing the force generation within each cycle.